Physical Evolution of the Last Melanau Communal Dwelling in Kampung Sok, Matu, Sarawak, Malaysia - Abdul Gapor, Salfarina; Moriat, Rahmat; Rahman, Haris Fadzilah Abdul; Saruan, Muhammad Ariff Mat (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2022)
The Melanau is one of the main ethnic groups in Sarawak. Historically, they lived in a communal dwelling, known as the tall house, designed to protect against the harsh micro-climate condition, wild animals and, enemies. Today, there are no visible remains of the tall house. The only tall house available in Sarawak is a reconstructed replica available at the Sarawak Cultural Village in Santubong, Kuching. However, there is one Melanau communal longhouse located at Kampung Sok, Matu, which has been gazetted under the Sarawak Cultural Heritage Ordinance 1993. The objective of this paper is to analyse the changes that the longhouse has experienced throughout the years. This study employs a qualitative approach through in-depth interviews with the owners of the longhouse. Data are also derived from measured drawings. Findings show that the characteristics of the longhouse are a hybrid of the Iban longhouse combined with the Melanau tall house and later with some Malay influences. This can be clearly seen from the spatial and functional analyses of the spaces as well as the general form of the building. The general form of the building resembles more towards the Iban longhouse, whereas the functional spaces are more towards the Melanau tall house. The 1930s renovation also shows influence from the Malay vernacular architecture through the introduction of change of level and secondary access. The findings also show that vernacular architecture evolves through time due to different needs, influences, and building materials.